Trust in the integrity of a micro health insurance scheme and its determinants in two rural districts of Ethiopia - Mohammed Hussien (BMC Health Services Research)
Abstract Background Mistrust in community-based health insurance schemes is a significant deterrent to enrollment and renewal decisions. Despite its significance, there is little evidence on the level of community trust in such schemes. This study examined the level of trust in the integrity of a community-based health insurance scheme and its determinants in two rural districts of northeast Ethiopia. Methods A community-based cross-sectional study was carried out on 1,232 randomly selected rural households who had been registered in a community-based health insurance scheme. The data were collected through face-to-face interviews using an electronic data collection platform. Multivariable ordinal logistic regression analysis was performed using the partial proportional odds model to examine predictors of trust. The degree of association was assessed using odds ratios, and statistical significance was determined at a 95% confidence interval. Results The mean score of the five trust dimensions was 5.86 on a scale of 0–10, ranging from 5.06 to 7.65. In the multivariable regression analysis, age (AOR = 1.58; 95% CI: 1.10, 2.29), female gender (AOR = 2.05; 95% CI: 1.29, 3.25), education (AOR = 1.36; 95% CI: 1.03, 1.80), insurance membership status (AOR = 2.68; 95% CI: 1.89, 3.80), membership duration (AOR = 1.51; 95% CI: 1.19, 1.92), value for solidarity (AOR = 1.71; 95% CI: 1.20, 2.45), perceived risk protection (AOR = 3.35; 95% CI: 2.27, 4.96), and perceived quality of care (AOR = 1.78; 95% CI: 1.34, 2.37) were positive predictors of trust in the integrity of the scheme, while wealth index (AOR = 0.33; 95% CI: 0.23, 0.47), and hospitalization history (AOR = 0.62; 95% CI: 0.48, 0.82) were negative predictors of trust. Conclusions Trust in the integrity of the scheme received mediocre scores, with some trust dimensions having lower ratings, indicating specific areas of focus to be considered in trust-building. Scheme administrators and health authorities need to devise strategies to improve people’s understanding of the basic principles of health insurance and promote access to high-quality care while minimizing expenditures at the point of receiving care.